THE EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON COMPANY STOCK PRICES: EMPIRICAL STUDY ON LQ45 COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2016-2020 PERIOD - Iskandar Zulkarnain; Wafiq Syifa Azzahra; Sjukun Sjukun (PENANOMICS: International Journal of Economics, 2022)
This study aims to determine theof Current Ratio and Debt to Equity Ratio.This research is a quantitative study using secondary data obtained through the financial statements of LQ45 company on the Indonesia Stock Exchange. The object of this research is LQ45 companies listed on the Indonesia Stock Exchange. The numbr of sample obtained in this study wer 10 companies. The sampling technique used was purposive sampling. Data analysis method used by the method of Multiple Linear Regression Analysis; the data obtained were then processed using SPSS (statistical Program of Social Science) software 20. The results showed that the Current Ratio has a positive and significant effect on stock price, the Debt-to-Equity Ratio has a negative and not significant effect on stock prices.